Investigating the Effects of Testosterone and Dihydrotestosterone on Atherogenesis in Normoglycemic and Hyperglycemic Mouse Models - Daniel Venegas-Pino; Brooke D’Mello; Mark De Leon; Geoff H. Werstuck (Endocrines)
Objective: The effect of testosterone on the development of cardiovascular disease (CVD) is of interest due to the higher risk of CVD in men. This study aims to examine the impact of testosterone depletion and supplementation on atherosclerosis progression in normoglycemic and hyperglycemic mouse models. Methods: Male apolipoprotein E-deficient (ApoE−/−) and hyperglycemic (insulin deficient) ApoE−/−Ins2+/Akita mice were fed a standard chow diet and were either castrated or subjected to sham operations at 5 weeks of age. At 8 and 16 weeks of age, subsets of these mice were implanted subcutaneously with a silastic tube containing either 40 µL of dihydrotestosterone (DHT, 25 mg/mL) or sesame oil as a vehicle control. Survival was monitored and all remaining mice were sacrificed at 24 weeks of age. Blood, heart, and aortic samples were collected for analysis. Metabolic parameters were evaluated, and atherosclerotic lesion volumes were measured at the aortic sinus and in en face whole aorta mounts. Results: Castration significantly promoted atherosclerosis in normoglycemic mice, with a 3.0-fold increase (p < 0.05) at the aortic sinus and a 3.5-fold increase (p < 0.05) in en face aortas. However, in hyperglycemic mice, castration attenuated atherosclerosis in en face aortas. Supplementation with exogenous DHT led to increased atherosclerosis in hyperglycemic mice and was associated with significant cardiac-related mortality in 21–24-week-old hyperglycemic mice. Conclusions: In this mouse model, while testosterone/DHT may offer cardioprotective benefits under normoglycemic conditions, it appears to exert substantial harmful effects, such as promoting atherosclerosis and increasing the risk of myocardial infarction, in hyperglycemic conditions.